'Agricultural Waste to Treasure' – Biochar and eggshell to impede soil antibiotics/antibiotic resistant bacteria (genes) from accumulating in Solanum tuberosum L. (November 2018) - Jiao, Wentao; Du, Ruijun; Ye, Mao; Sun, Mingming; Feng, Yanfang; Wan, Jinzhong; Zhao, Yuanchao; Zhang, Zhongyun; Huang, Duan; Du, Daolin; Jiang, Xin
Abstract: Soil contamination with antibiotics and antibiotic resistant bacteria/genes (ARB/ARGs) has becoming an emerging environmental problem. Moreover, the mixed pollutants' transfer and accumulation from soil to tuberous vegetables has posed a great threat against food security and human health. In this work, the application of two absorbing materials (maize biochar and sulfate modified eggshell) was able to reduce the poisonous effect of soil antibiotics on potato root system by stimulate the dissipation of water-soluble antibiotics in soil; and also improve food quality by increasing potato starch, protein, fat, and vitamins. Meanwhile, both amendments could effectively decrease the classes and the accumulative abundance of ARB and ARGs ( sul I, sul II, cat I, cat II, erm A, erm B) in the edible parts of potato. The lowest abundance of ARGs was detected in the biochar application treatment, with the accumulative ARG level of 8.9 × 10 2 and 7.2 × 10 2 copies mL −1 in potato peel ( sul l +  cat I +  erm A) and tuberous root ( sul I), respectively. It is the first study to demonstrate the feasibility of biochar and eggshell derived from agricultural wastes as green absorbing materials to reduce soil antibiotic, ARB, and ARGs accumulation risk in tuberous vegetable. Graphical abstract: Image 1 Highlights: Biochar or eggshell impeded soil antibiotics accumulation in potato effectively. ARB isolates in potato decreased significantly after biochar or eggshell addition. ARG accumulation risk was limited in potato with biochar or eggshell amendment. Impedance effect of biochar was more effective than that of eggshell. Biochar or eggshell application provided new strategy to ensure vegetable security. Abstract : ARB and ARG accumulation risk was limited in potato with biochar or eggshell amendment; Impedance effect of biochar was more effective than that of eggshell.